Case report: Infantile pulmonary alveolar proteinosis associated with cytosolic isoleucyl-tRNA synthetase deficiency - Wu, Jie; Fan, Yimu; Huo, Feng; Deng, Jie; Wang, Quan; Shen, Yuelin (Frontiers in Pharmacology, 2025)
Cytosolic isoleucyl-tRNA synthetase (IARS1) deficiency, an exceptionally rare autosomal recessive inherited disorder, is characterized by multiple system involvement, including growth retardation, intellectual developmental disorder, hypotonia, and hepatopathy. Pulmonary alveolar proteinosis (PAP) is a rare phenotype of IARS1 deficiency, having been reported in only two siblings from the same family. In this study, we present a case of IARS1 deficiency in a 5-month-old boy, who exhibited PAP as the initial and predominant manifestation. Additionally, whole-exome sequencing identified compound heterozygous variants in the IARS1 gene (c.2428C>T/c.128T>C), both of which are novel observations.